Analysis of determinants of banking company's financial performance during the covid-19 pandemic - Cindy Karmilasari; Imam Agus Faisol (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2023)
During the Covid-19 pandemic, the banking sector was extremely susceptible to losses because so many debtors from diverse industrial sectors were afflicted by Covid-19 and had difficulty meeting their obligations. This study aims to examine the impact of Good Corporate Governance, capital structure, and company size on the 2020 financial performance of Indonesia Stock Exchange-listed banking companies. In this study, the independent board of commissioners, board of directors, audit committee, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and company size are the independent variables. In this study, the dependent variable is the company's financial performance (ROA). This study employed a technique of purposive sampling to collect 46 samples. The method of analysis employed is multiple linear regression analysis. The results show that the independent board of commissioners, Debt to Equity Ratio, and company size positively affect financial performance. The Board of directors and audit committee has no significant effect on financial performance. Meanwhile, the Debt to Asset Ratio harms financial performance.